ACCELERATING STUDENTS’ CAPABILITIES IN ACCOMPLISHING FINAL PAPERS: AN EVALUATION - Fadly Azhar; Putri Yuanita; Erni Erni; Novitri Novitri (International Journal of Educational Best Practices, 2021)
This paper aimed at evaluating such aspects as self-efficacy, research methodology, types of supervisor, and academic writing ability in accelerating students accomplishing final papers. 214 students of bachelor and master programs at Universitas Riau - Indonesia were selected through purposive sampling technique as the participants. This research used Context, Input, Process, and Product Evaluation Model to evaluate those variables. The research findings revealed that (a) there was no significant difference in self-efficacy on the aspects of gender ((sig. 0.219 > p 0.05) and learning support facilities ((sig. 0.073 > p  0.05); (b) in research methodology on the aspect of gender ((sig. 0.508 > p 0.05); (c) in academic writing ability on the aspects of gender (sig. 0.939 > p 0.05); and (d) in types of supervisors on the aspects of gender (sig.0.618 > p 0.05), sources of educational cost (sig. 0.474 > p 0.05), and learning support facilities (sig. 0.773 > p 0.05). However, (a) there was a significant difference in self-efficacy on the aspects of profession (sig. 0.000 < p 0.05), and sources of educational cost (sig. 0.014 < p 0.05); (b) in research methodology on the aspects of profession (sig. 0.000 < p 0.05), sources of educational cost (sig. 0.004 < p 0.05), and learning support facilities (sig. 0.001 < p 0.05); (c) in academic writing ability on the aspects of profession (sig. 0.013 < p 0.05 ), sources of educational support (sig. 0.014 < p 0.05), and learning support facilities (sig. 0.000 < p 0.05); and (d) in types of supervisors on the aspect of profession (sig. 0.022 < p 0.05). Partially, self-efficacy contributed 59.7%; research methodology (10.4%) and types of supervisor (0.1%) ---- which is totally 70.2% towards the students’ academic writing ability in accelerating students accomplishing final papers.